Ambiguity of curator’s authority in implementing sales of collateral objects on behalf of third parties in bankruptcy proceedings - Yuhelson, Yuhelson; Retnaningsih, Sonyendah (Edelweiss Applied Science and Technology, 2025)
Curators play a pivotal role in the bankruptcy process, tasked with managing and settling bankrupt assets. However, there exists ambiguity regarding the curator’s authority in executing the sale of collateral objects on behalf of third parties. This study aims to analyze the regulations and authority of curators, as well as the legal certainty for curators in settling or selling collateral objects on behalf of third parties within the bankruptcy process. The current research employs a normative legal research methodology, utilizing a statutory approach and case studies. The findings reveal that curators are authorized to sell bankrupt assets through open auctions while adhering to the principles of bankruptcy. Nevertheless, regulatory changes concerning document requirements for auctioning third-party assets have led to legal uncertainty. Clear and firm regulations are necessary to enable curators to sell collateral objects on behalf of third parties without requiring proof of rights transfer, by completing alternative documents such as a statement letter and the determination of the supervisory judge. Harmonization of these regulations is expected to establish legal certainty for curators in carrying out their duties.